The development of the cluster of wooden construction as the direction of the innovative strategy of the Russian timber industry complex - A. Z. Gusov; A. V. Smirnov (Путеводитель предпринимателя)
The article analyses the basic problems of cluster development of wooden housing construction as to one of directions of increase of stability and competitiveness of the Russian timber industry complex in conditions of development of modern innovative economy.